TYPE OF HEROISM OF MAIN CHARACTER AND THE CAUSE OF EMERGENCE OF HEROISM IN THE MOVIE ‘PERCY JACKSON : SEA OF MONSTERS.’ - Ria Yuliasari; Rika Virtianti (Universitas Nasional, 2021)
The research aims at analyzing the types of heroism of the main character and the cause of the emergence of the heroism in the movie ‘Percy Jackson Sea of Monster’. The research method used is descriptive qualitative to analyze the type of heroism of the main character and the cause of the emergence of the hero in the book. Analysis of the type of heroism is carried out using the Morison and Labiak’s theory, while analysis of the cause of emergence of the hero is carried out using Restivo and Cherry’s theory. Observations show that the hero in the book is the main character, Percy Jackson, and the type of heroism belongs to the type of perfect hero and epic hero. The observations also show that there are two factors that cause the emergence of the heroism which are bad situation, injustice and self-sacrifice.Keywords: type of heroism, main character and cause of the emergence of the heroism